Effects of hydrostatic high pressure on microbiological and technological characteristics of beer - Fischer, Steffen; Ruß, Winfried; Roman Buckow, Roman Buckow; Heinz, Volker; Ulmer, Harald; Behr, Jürgen; Meyer-Pittroff, Roland; Knorr, Dietrich; Vogel, Rudi F. (BrewingScience, 2006)
High pressure treatment is well known as a sparing method for the preservation of beverages or food with low pH value, because it has only little effects on color, aromatic compounds and valuable substances like vitamins. Beer has a very sensitive composition and therefore high pressure treatment is an interesting preservation technique.This study consisted of three parts: The effect of high pressure/temperature combinations was determined on the enzymes β-amylase, amyloglucosidase and β-glucanase. The mathematical modeling of the empirically detected results allowed the calculation of pressure/temperature combinations for varying treatment times which result in different activity, substrate conversion or stability. It was possible to detect an area with maximized substrate conversion for β-amylase extracted from barley malt. Amyloglucosidase shows higher activity at high pressure and high temperature and also β-glucanase reacts faster with increased pressure and temperature. On this basis, the mashing time could be shortened significantly by applying pressure of about 100 to 150 MPa.Another step during the brewing process which was effected positively by high pressure treatment was the filterability. Independent of prevailing beer filtration problems it was possible to improve the filterability, regardless if the analyses were carried out with cellulose filter pads or kieselguhr. The influenced parameter was the content of β-glucan gel. In beer and in model systems with very high concentrations, a degradation of β-glucan gel was detected. Using different analytical systems it could be shown that β-glucan was formed. The third effect of high pressure was the inactivation of beer spoiling lactobacilli. These microorganisms are tolerant against hop ingredients and low pH values in beer. High pressure treatment at 200 MPa of Lactobacillus plantarum and L. brevis showed no significant decrease in the surviving cell counts, but after a few hours of storage in presence of hop the damaged L. plantarum cells died, whereas highly hop tolerant L. brevis cells survived. Therefore, it is necessary to inactivate highly hop tolerant L. brevis. A degradation of 5 powers of ten was possible with 40 °C at 400 MPa for 30 s.